Origin of the 30 THz Emission Detected During the 2012 March 13 solar flare at 17:20 UT - Trottet, G. (2015)
Solar observations in the infrared domain can bring important clues on the response of the low solar atmosphere to primary energy released during flares. At present, the infrared continuum has been detected at 30 THz (10 μm) in only a few flares. SOL2012-03-13, which is one of these flares, has been presented and discussed in Kaufmann et al. (Astrophys. J.768, 134, 2013). No firm conclusions were drawn on the origin of the mid-infrared radiation. In this work we present a detailed multi-frequency analysis of the SOL2012-03-13 event, including observations at radio-millimeter and submillimeter wavelengths, in hard X-rays (HXR), gamma-rays (GR), HαHα , and white light. The HXR/GR spectral analysis shows that SOL2012-03-13 is a GR line flare and allows estimating the numbers of and energy contents in electrons, protons, and αα particles produced during the flare. The energy spectrum of the electrons producing the HXR/GR continuum is consistent with a broken power-law with an energy break at ∼800 keV∼800 keV . We show that the high-energy part (above ∼800 keV∼800 keV ) of this distribution is responsible for the high-frequency radio emission ( >20 GHz>20 GHz ) detected during the flare. By comparing the 30 THz emission expected from semi-empirical and time-independent models of the quiet and flare atmospheres, we find that most ( ∼80 %∼80 % ) of the observed 30 THz radiation can be attributed to thermal free–free emission of an optically thin source. Using the F2 flare atmospheric model (Machado et al. in Astrophys. J.242, 336, 1980), this thin source is found to be at temperatures T ∼8000 K∼8000 K and is located well above the minimum temperature region. We argue that the chromospheric heating, which results in 80 % of the 30 THz excess radiation, can be due to energy deposition by nonthermal flare-accelerated electrons, protons, and αα particles. The remaining 20 % of the 30 THz excess emission is found to be radiated from an optically thick atmospheric layer at T ∼5000 K∼5000 K , below the temperature minimum region, where direct heating by nonthermal particles is insufficient to account for the observed infrared radiation.